Reduction of Macrophage Infiltration and Chemoattractant Gene Expression Changes in White Adipose Tissue of Morbidly Obese Subjects After Surgery-Induced Weight Loss - Cancello, Raffaella; Henegar, Corneliu; Viguerie, Nathalie; Taleb, Soraya; Poitou, Christine; Rouault, Christine; Coupaye, Muriel; Pelloux, Veronique; Hugol, Danielle; Bouillot, Jean-Luc; Bouloumié, Anne; Barbatelli, Giorgio; et al. (Diabetes (New York, N.Y.), 2005)
Reduction of Macrophage Infiltration and Chemoattractant Gene Expression Changes in White Adipose Tissue of Morbidly Obese Subjects After Surgery-Induced Weight Loss Raffaella Cancello 1 , Corneliu Henegar 1 2 , Nathalie Viguerie 3 , Soraya Taleb 1 , Christine Poitou 1 , Christine Rouault 1 , Muriel Coupaye 1 , Veronique Pelloux 1 , Danielle Hugol 4 , Jean-Luc Bouillot 5 , Anne Bouloumié 3 6 , Giorgio Barbatelli 7 , Saverio Cinti 7 , Per-Arne Svensson 8 , Gregory S. Barsh 9 , Jean-Daniel Zucker 1 10 , Arnaud Basdevant 1 , Dominique Langin 3 and Karine Clément 1 1 Inserm “Avenir”, Paris 6 University EA3502 and Human Research Center on Nutrition (CRNH), Hôtel Dieu Hospital, AP/HP, Paris, France 2 SPIM “Santé publique et informatique médicale” laboratory, INSERM ERM202, Paris, France 3 INSERM UPS U586, Obesity Research Unit, Louis Bugnard Institute, Paul Sabatier University, Toulouse, France 4 Department of Anatomo-Pathology, Hôtel Dieu Hospital, Paris, France 5 Department of Surgery, Hôtel Dieu Hospital, Paris, France 6 Cardiovascular Physiology Department, J.-W. Goethe University, Frankfurt, Germany 7 Institute of Normal Human Morphology-Anatomy, School of Medicine, Polytechnic University of Marche, Ancona, Italy 8 Department of Internal Medicine, Research Centre for Endocrinology and Metabolism, Sahlgrenska Academy, Goteborg University, Goteborg, Sweden 9 Department of Pediatrics and Genetics, Howard Hugues Medical Institute, Beckman Center, Stanford University School of Medicine, Stanford, California 10 LIM & BIO, Paris-Nord University, Paris, France Address correspondence and reprint requests to Karine Clément, MD, PhD, Department of Nutrition, Hôtel-Dieu Hospital, 1, Place du Parvis Notre-Dame, 75004 Paris, France. E-mail: karine.clementathtd.ap-hop-paris.fr Abstract In human obesity, the stroma vascular fraction (SVF) of white adipose tissue (WAT) is enriched in macrophages. These cells may contribute to low-grade inflammation and to its metabolic complications. Little is known about the effect of weight loss on macrophages and genes involved in macrophage attraction. We examined subcutaneous WAT (scWAT) of 7 lean and 17 morbidly obese subjects before and 3 months after bypass surgery. Immunomorphological changes of the number of scWAT-infiltrating macrophages were evaluated, along with concomitant changes in expression of SVF-overexpressed genes. The number of scWAT-infiltrating macrophages before surgery was higher in obese than in lean subjects (HAM56+/CD68+; 22.6 ± 4.3 vs. 1.4 ± 0.6%, P < 0.001). Typical “crowns” of macrophages were observed around adipocytes. Drastic weight loss resulted in a significant decrease in macrophage number (−11.63 ± 2.3%, P < 0.001), and remaining macrophages stained positive for the anti-inflammatory protein interleukin 10. Genes involved in macrophage attraction (monocyte chemotactic protein [MCP]-1, plasminogen activator urokinase receptor [PLAUR], and colony-stimulating factor [CSF]-3) and hypoxia (hypoxia-inducible factor-1α [HIF-1α]), expression of which increases in obesity and decreases after surgery, were predominantly expressed in the SVF. We show that improvement of the inflammatory profile after weight loss is related to a reduced number of macrophages in scWAT. MCP-1, PLAUR, CSF-3, and HIF-1α may play roles in the attraction of macrophages in scWAT. CRP, C-reactive protein CSF, colony-stimulating factor GO, Gene Ontology Consortium FDR, false discovery rate HIF-1α, hypoxia-inducible factor-1α IL, interleukin MCP, monocyte chemotactic protein ORO, orosomucoid PLAUR, plasminogen activator urokinase receptor RTqPCR, real-time quantitative PCR SAA, serum amyloid A SAM, significance analysis of microarrays scWAT, subcutaneous WAT SVF, stroma vascular fraction WAT, white adipose tissue Footnotes The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “ advertisement ” in accordance with 18 U.S.C. Section 1734 solely to indicate this fact. Accepted May 16, 2005. Received January 17, 2005. DIABETES